DTIE, a novel core promoter element that directs start site selection in TATA-less genes - Marbach-Bar, Nadav (Nucleic Acids Res, 2016)
The transcription start site (TSS) determines the length and composition of the 5′ UTR and therefore can have a profound effect on translation. Yet, little is known about the mechanism underlying start site selection, particularly from promoters lacking conventional core elements such as TATA-box and Initiator. Here we report a novel mechanism of start site selection in the TATA- and Initiator-less promoter of miR-22, through a strictly localized downstream element termed DTIE and an upstream distal element. Changing the distance between them reduced promoter strength, altered TSS selection and diminished Pol II recruitment. Biochemical assays suggest that DTIE does not serve as a docking site for TFIID, the major core promoter-binding factor. TFIID is recruited to the promoter through DTIE but is dispensable for TSS selection. We determined DTIE consensus and found it to be remarkably prevalent, present at the same TSS downstream location in ≈20.8% of human promoters, the vast majority of which are TATA-less. Analysis of DTIE in the tumor suppressor p53 confirmed a similar function. Our findings reveal a novel mechanism of transcription initiation from TATA-less promoters.